New electrocardiographic score for the prediction of atrial fibrillation: The MVP ECG risk score (morphology‐voltage‐P‐wave duration). Issue 6 (11th June 2019) - Alexander, Bryce; Milden, Julia; Hazim, Bachar; Haseeb, Sohaib; Bayes‐Genis, Antoni; Elosua, Roberto; Martínez‐Sellés, Manuel; Yeung, Cynthia; Hopman, Wilma; Bayes de Luna, Antoni; Baranchuk, Adrian
Abstract: Background: Atrial fibrillation (AF) is the most common arrhythmia and has significant morbidity. A score composed of easily measured electrocardiographic variables to identify patients at risk of AF would be of great value in order to stratify patients for increased monitoring and surveillance. The purpose of this study was to develop an electrocardiographic risk score for new‐onset AF. Methods: A total of 676 patients without previous AF undergoing coronary angiography were retrospectively studied. Points were allocated based on P‐wave morphology in inferior leads, voltage in lead 1, and P‐wave duration (MVP). Patients were divided into three risk groups and followed until development of AF or last available clinical appointment. Results: Mean age was 65 years, and 68% were male. The high‐ and intermediate‐risk groups were more likely to develop AF than the low‐risk group (odds ratio [OR] 2.4, 95% confidence interval [CI] 1.3–4.4; p  = 0.006 and OR 2.1, 95% CI 1.4–3.27; p  = 0.009, respectively). The high‐risk group had a significantly shorter mean time to development of AF (258 weeks; 95% CI 205–310 weeks) compared to the intermediate‐ (278 weeks; 95% CI 252–303 weeks) and low‐risk groups (322 weeks 95% CI 307–338 weeks), p  = 0.005. Conclusions: A simple risk score composed of easy‐to‐measure electrocardiographic variables can help to predict new‐onset AF. Further validation studies will be needed to assess the ability of this risk score to predict AF in other populations.